Comparison of modelling and prediction of export values in West Java, Banten, and Central Java using the STIMA and GSTIMA (1, 1, 1). (2022) - Zebua, Hasrat Ifolala; Simatupang, Marnita; Ghifari, Abdurrahman Al; Ningtias, Yunita Dwi Ayu; Toharudin, Toni; Ruchjana, Budi Nurani
No abstract available